An Orphan Pheromone Receptor Affects the Mating Behavior of Helicoverpa armigera - Cao, Song; Huang, Tianyu; Shen, Jie; Liu, Yang; Wang, Guirong (Frontiers in Physiology, 2020)
The Lepidoptera is the second largest insect order, which has the most extensive knowledge of sex pheromones and mechanisms of pheromone communication since the identification of the first insect pheromone in Bombyx mori. In the past 15 years, pheromone receptors have been identified and functionally characterized in many moth species. HarmOR14 is a typical pheromone receptor of Helicoverpa armigera which showed no response to the tested pheromones in Xenopus oocyte expression system, but its orthologous gene in Heliothis virescens, HvirOR14 could be activated by pheromones in the same expression system. To assess the possible functions of OR14 in vivo, in this study, we knocked out this gene using CRISPR/Cas9 system and compared the mating behaviors and EAG response to pheromones between the wild type and mutant strains. Our results showed that OR14 mutants did not affect the mating rate or the EAG response to pheromones but could prolong the mating duration and change the mating time in undefined manners, which extends our understanding to this kind of pheromone receptors.